KENDALI GERAK ROBOT HEXAPOD MENGGUNAKAN REMOTE CONTROL BERBASIS ANDROID - Rendyansyah; Huda Ubaya; Amrial Faydinar; Yurias Ramdhan (J-Innovation, 2018)
The development of technology can help human work, one of which is robot technology that can be used in the military and security fields.As in the application of robot in the military field is a robot for investigating an arena or object. This robot is generally controlled using remote control and even the use of mini computer to monitor the unpredictable environment. In the other hand, the use of legged robot like the hexapod robot is also used to search target, investigation, and others. In this research, hexapod robot has been equipped with Arduino Uno module, servo motor driver, servo motors, and integrated with power supply. Hexapod robot is controlled manually using a remote control based on an Android smartphone, and the communication use Bluetooth. The robot has implanted the logic of movement forward, backward, turn right and left, which movement is active if given an order by the user using Android. For the robot move forward by sending the character "A", the robot move backward by sending the character "B", and to turn left and right respectively by sending the characters "C" and "D". The experimental results show that hexapod robot and android smartphone are connected properly, and the robot has successfully moveforward, backward, turn left and right according to the commands given to the robot.